PENGEMBANGAN E-MODUL PADA MATA PELAJARAN TEKNIK GAMBAR MANUFAKTUR DI SMKS DHUAFA PADANG - Syafriade Putra; Eko Indrawan; Delima Yanti Sari (Jurnal Vokasi Mekanika (VoMek), 2024)
The learning media used previously for the Manufacturing Drawing Technique subject in class XI of Machining Engineering has not been optimal in achieving learning objectives. Therefore, this research aims to develop e-modules as learning media at SMKS Dhuafa Padang. The research used an R&D development model in education based on the IDI model, which was carried out in the odd semester of FY 2023/2024. The IDI model includes three stages: determination, development, and assessment. Data were collected through a validation sheet in the form of a questionnaire and analyzed with quantitative descriptive statistics. The results showed that this e-module was feasible to use as an independent learning media with a final validity value of 0.83 from material experts and 0.90 from media experts, which met the valid criteria. The e-module practicality test showed very practical results, with an average percentage value of 93.6% from the teacher's assessment. The use of this e-module is expected to provide several significant advantages for the learning process. First, this e-module allows more flexible access to learning for students, allowing them to learn anytime and anywhere at their convenience. Secondly, interactive and engaging e-modules are expected to increase students' motivation and interest in learning. Thus, this e-module not only helps students understand the subject matter better but also supports the development of self-learning skills essential for long-term academic success.